Spatial Transformation at Wonosari Tea Factory as Industrial Space - Fadilah, Saniatul (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, 2024)
Black tea as an export commodity in Indonesia has a long history dating back to the Dutch East Indies. The existence of tea factories is closely related to the industrial revolution in the 19th century where there were large-scale production activities in the Java and Sumatra regions. The formation of space in the black tea factory is a long history involving the evolution of the industry over time. The rapid development of manufacturing and technology requires many modifications to the spatial space. It is certainly very influential on the spatial aspects of a tea factory as well as being a rarity value in an industrial process, landscape value and providing social identity value in industrial heritage buildings. The purpose of this study is to determine the spatial transformation and the factors that influence it. This research was conducted at Wonosari Tea Factory in Malang Regency using analytical descriptive method through interpretation. The conclusion that can be drawn from is that Wonosari Tea Factory has undergone significant spatial changes, the changes are clearly visible in the relationship between spaces, space area and space patterns used. The main factors that cause changes are caused by the use of technology, capacity and production standards applied. Other factors that cause changes are architectural style, ownership, socio-economic conditions and community culture and natural conditions. Keywords: Spatial transformation, industrial space, tea factory